The Impact of Accounting Information Systems, Internal Controls, and Digital Transformation on Financial Performance in Semarang's Furniture Industries - Dian Tantri Arifia; RR. Supratiningrum; Janti Soegiastuti; Parju Parju (International Journal of Economics and Management Research, 2026)
This research is motivated by the fluctuating financial performance in the furniture industry in Semarang City, amidst the pressures of digitalization and strengthening internal governance. Based on the Technology Acceptance Model (TAM), which posits that technology acceptance through perceptions of usefulness and ease of use can influence organizational performance, this study aims to examine the impact of Accounting Information Systems (AIS), Internal Control Systems (ICS), and Digital Transformation on financial performance in the furniture industry. Using a quantitative approach with multiple linear regression, the study sampled all 61 furniture companies in Semarang City. The results from the partial test (t-test) reveal that AIS has a positive but insignificant effect on financial performance (t=0.485; sig=0.629), ICS has a positive but insignificant effect (t=1.827; sig=0.073), while Digital Transformation has a positive and significant effect (t=4.516; sig=0.000). These findings suggest that digital transformation is the dominant factor in improving financial performance, while AIS and ICS have not yet had a significant impact. The study recommends improving digital literacy, strengthening AIS implementation, and integrating ICS for more sustainable financial performance.